THE IDENTIFICATION OF COMPONENTS, LANGUAGE FUNCTIONS, AND LANGUAGE EXPRESSIONS OF LOVINA DOLPHIN TOUR WEBSITES - Wahyudi, Gede; Putu, Ayu Prabawati Sudana; Sari, Rima Andriani (Lingua Scientia, 2025)
This study aims to identify the components, language functions, and language expressions used on Lovina Dolphin Tour websites. The research used qualitative design because all the data obtained are in the forms of words not numbers. The writers used sentence from the websites as a source of the data. Using the Observation Sheet, the researcher analyzed content from five selected websites. The findings reveal six main components: transportation, lodging, dining, sightseeing/guide services, attractions, and shopping. Additionally, nine language functions were identified, including introducing, informing, persuading, giving advice, describing actions, describing guest services, describing guest attractions, explaining places, describing people, expressing opinions, and drawing conclusions. A total of 38 language expressions were found across the websites. These expressions primarily serve to explain and promote the tour packages offered, helping potential visitors understand the services and experiences available. Overall, the study highlights how tourism websites strategically use language to present information clearly and persuasively.